Unusual presentation of an obstetrical urethrovaginal fistula secondary to improper catheter placement - Cameron, Anne P.; Atiemo, Humphrey O. (Canadian Urological Association Journal, 2013)
Vesicovaginal and urethrovaginal fistulas related to obstetrical causes are exceptionally rare in the developed world. We report a case of 23-year-old woman with a urethrovaginal fistula, which developed after a cesarean delivery because of an inappropriately placed urethral catheter. Diagnostic evaluation and surgical approach are discussed.